miRNA-mediated deregulation in leukemia - Dell'Aversana, Carmela; Altucci, Lucia (Frontiers in Genetics, 2012)
MicroRNAs (miRNAs) are small non-coding RNAs 18 to 22 nucleotides (nt) long able to fine-tune post-transcriptional gene expression. Extensive investigation intobiogenesis, mechanism of action and functions of miRNAs has clearly revealed their prompt control in developmental timing, differentiation, proliferation, cell death and metabolism. Deregulationof miRNA-mediated pathways may contribute to pathological conditions such as tumors, including hematological cancer, thus suggesting that miRNAs act both as tumor-suppressor genes (TSG) and oncogenes (OG).Here, we provide an overview of the current understanding of the aberration of miRNA biogenesis, activity and post-transcriptional control in leukemogenesis.